MICROSCOPIC, PHYSICOCHEMICAL AND PHYTOCHEMICAL SCREENING OF CRATEVA MAGNA (LOUR) DC. (LEAF) - J., Abirami; G., Jothi; P., Brindha (International Journal of Current Pharmaceutical Research, 2017)
Objective: Preliminary screening of phytochemicals is a valuable step, in the detection of the bioactive principles present in medicinal plants and subsequently may lead to drug discovery and development. In the present study, the identity, purity and strength of Crateva magna (Lour) DC. (Leaf), HPTLC, LC MS and phytochemical screening were analysed. Methods: Tests for Identity, Purity, and Strength of Crateva magna (Lour) DC. (Leaf) Botanical standards, Physicochemical constants such as Foreign matter, Total ash, moisture content, Acid insoluble ash, and water soluble ash and Extractive value such as Hexane, Chloroform, Ethyl acetate, Alcohol were determined. The Preliminary Phytochemical Analysis of various extracts was also determined. HPTLC, LCMS ANALYSIS was analysed. Results: Microscopic studies T S of Crateva magna leaf shows the presence of prominent midrib, upper and lower epidermis and lamina. Preliminary phytochemical analysis of dry powder and aqueous extracts of Crateva magna (Lour) DC. (Leaf) showed the presence of flavones, steroids, glycosides, sugar, alkaloids, quinones, phenols, coumarin and lignin. HPTLC of an Aqueous extract of the Crateva magna (Lour) DC. (Leaf). LC MS spectrum indicates may be the presence of bioactive compounds. Conclusion: The results revealed that aqueous extract of Crateva magna (Lour) DC. (Leaf) has suitable for anti ulcer study.